The Influence of Competence and Organizational culture on Job Satisfaction and Employee Performance in the Culture Office of Denpasar City - Anak Agung Ayu Ketut Sarhi Lestari; I. B Agung Dharmanegara; I Wayan Gde Sarmawa; Nyoman Hendra Laksmana (Global Researcher Network, 2022)
In the regional apparatus organization, human resources play a role in achieving work plans that have been made and compiled in the form of programs and activities, in this case having an important role in conducting public services. Employee performance in regional apparatus organizations refers to employee work performance or work appraisal or the so-called Employee Work Target (SKP) consisting of work contracts, measurement and work performance appraisal. Performance appraisal is an important key that can describe the performance and results achieved by a government agency and is expected to reveal an overall accountability from the beginning of planning, monitoring to evaluation. The aim of this research was to determine and explain the influence of organizational competence and culture on job satisfaction and employee performance at the Denpasar City Culture Office. The populations in this research were all Civil Servants of the Denpasar City Cultural Office with a sample of 38 people. A data collection technique wasused observation, interviews and surveys. The results showed that competence had no significant negative effect on job satisfaction, competence had a significant positive effect on employee performance, organizational culture had a significant positive effect on job satisfaction, organizational culture had a significant positive effect on employee performance and job satisfaction had no significant positive effect on employee performance.